La clase, lugar de encuentros. (2021)
How to understand the relationship that is established among teacher - pupil in the context of the audio-visual production class? That is one of the matters that I want to develop in this article, beginning from the class as a generator space of a dialogical process among the people that intervene there. People who are subjected by their personal experience, the social institutions and the cultural transformations of the social context nowadays. This is way, the teacher not only should design his objectives and formation competences but also, should ask himself about the expectations and aesthetic explorations of his pupils, due to they are aspects that are the basis to the active construction of the dynamics in class.